Community perception of barriers and facilitators to institutional delivery care-seeking behavior in Northwest Ethiopia: a qualitative study - Adane Nigusie; Telake Azale; Mezgebu Yitayal; Lemma Derseh (BMC, 2022)
Plain language summary Institutional delivery plays a critical role in the prevention of maternal death and improves newborn health. Although most of maternal health services were free of charge in Ethiopia, institutional delivery is low in the rural Central Gondar zone of Wogera and East Dembiya districts. Low institutional delivery was the major contributors to high maternal deaths in Ethiopia. This low utilization of institutional delivery in the study area could also affect the health status of the newborn. This study was conducted to explore the community perceptions of the socio-cultural and health service factors influencing institutional delivery. Overall, 30 interviews (18 In-depth and 12 Key-informants) were conducted in the selected rural kebeles of Wogera and East Dembiya districts to collect data from women and their husbands for in-depth interview; and key informant interviews from the female health development army and health extension workers. The facilitators of institutional delivery categorized into three themes; namely, free maternal services (ambulance services and maternity services), having the experience of safe childbirth at health facilities, and women's health development army linkage with health extension workers. The socio-cultural factors impeding institutional delivery categorized into five themes; namely, the belief that pregnancy and childbirth are normal and business of women's, women's preference of home delivery with traditional attendants, family influence, fear of bad behavior of health care workers, and lack of resources. Conducting a stage-matched intervention shall be designed to improve the uptake of institutional delivery service use in Wogera and East dembiya districts.